Democratic sanctions meet black knight support: revisiting the Belarusian case. Issue 3 (3rd April 2019) - Sejersen, Mikkel
ABSTRACT: Democracy promotion through economic sanctions has become commonplace. Previous studies argue that an important challenge to the effectiveness of democratic sanctions is the contravening support of black knights. However, these studies underestimate conflicting interests between the target and its black knight. In this paper, I propose a bargaining model for understanding how targets obtain support from black knights. The target's main source of bargaining power is its threat to defect from the black knight and obtain support from an international rival. However, the credibility of this threat decreases with democratic sanctions because they hinder cooperation with a likely source of support, namely the sender. Therefore, targets take steps towards democracy to improve their bargaining position relative to the black knight. To probe my argument, I conduct a deep single case study of EU sanctions against Belarus between 2004 and 2016 with Russia as a black knight. Sanctions should have no effect in this paradigmatic case of black knight support. Yet, there is substantial evidence that democratic sanctions have increased the cost of electoral fraud and state repression in Belarus. This indicates that the conflicting interests of targets and their black knights provide windows of opportunity for democracy promotion.